A study on macroeconomic variables affecting household debt in Malaysia / Siti Norsakinah Ajis - Ajis, Siti Norsakinah (Faculty of Business and Management, 2020)
This study is conducted to identify the relationship between macroeconomics variables which are House Price Index (HPI), Interest Rate (INT), Gross Domestic Product (GDP), and unemployment rate (UR) towards the Household Debt (HD) in Malaysia. The quarterly data of dependent and independent variables was collected started from Q1 2008 until Q4 2018 from Thomson Reuters, National Property Information Centre (NAPIC), Tradingeconomics.Com and Bank for International Settlements. The results further our understanding regarding on the relationship between macroeconomics variables towards the Household Debt in Malaysia. In Multiple Linear Regression (MLR), the study found that Interest Rate (INT) and unemployment rate (UR) have significant negative relationship towards Household Debt (HD). On the other hand, House Price Index (HPI) and Gross Domestic Product (GDP) shows significant positive relationship with Household Debt (HD).